Re-evaluation of the Bahariya Formation carcharodontosaurid (Dinosauria: Theropoda) and its implications for allosauroid phylogeny. - Maximilian Kellermann; Elena Cuesta; Oliver W M Rauhut (PLoS ONE)
The first partial skeleton of a carcharodontosaurid theropod was described from the Egyptian Bahariya Oasis by Ernst Stromer in 1931. Stromer referred the specimen to the species Megalosaurus saharicus, originally described on the basis of isolated teeth from slightly older rocks in Algeria, under the new genus name Carcharodontosaurus saharicus. Unfortunately, almost all of the material from the Bahariya Oasis, including the specimen of Carcharodontosaurus was destroyed during World War II. In 1996, a relatively complete carcharodontosaurid cranium was described from similar aged rocks in Morocco and designated the neotype of the species Carcharodontosaurus saharicus in 2007. However, due to the destruction of the original material, comparisons of the neotype to the Egyptian fossils have so far only been done cursorily. A detailed reexamination of the available information on the Egyptian carcharodontosaurid, including a previously undescribed photograph of the exhibited specimen, reveals that it differs from the Moroccan neotype in numerous characters, such as the development of the emargination of the antorbital fossa on the nasals, the presence of a horn-like rugosity on the nasal, the lack of a dorsoventral expansion of the lacrimal contact on the frontals, and the relative enlargement of the cerebrum. The referability of the Egyptian specimen to the Algerian M. saharicus is found to be questionable, and the neotype designation of the Moroccan material for C. saharicus is accepted here under consideration of ICZN Atricle 75, as it both compares more favorably to M. saharicus and originates from a locality closer to the type locality. A new genus and species, Tameryraptor markgrafi gen. et sp. nov, is proposed for the Egyptian taxon. The theropods of the Bahariya Oasis and the Moroccan Kem Kem Group are thus not as closely related as previously thought, and the proposed faunal similarities between these two strata need further examination.